CONVERGENCE OF CONTEMPORARY LEGAL SYSTEMS (BASED ON THE EXAMPLE OF EUROPE, AFRICA, THE US, AND SOME MUSLIM COUNTRIES) - Shestak, Victor; Grishnova, Elena; Muratova, Elena; Panov, Evgeny (Revista Inclusiones, 2020)
The relevance of the study of the convergence of contemporary legal systems is due, on the one hand, to the interpenetration of the legal norms of various legal systems (legal families) in recent decades and the blurring of the boundaries of legal systems and on the other hand, to the processes of law codification that have taken place in different countries in recent years and decades. The objective of the article is to find the optimal ways of convergence of contemporary legal systems on the example of some European countries (European Union), the US, as well as some African and Muslim countries. The deductive method was the leading method in the research, which made it possible to study the legal nature of the convergence of modern legal systems. The article concludes that the legislation in the US legal system has a more specific weight and is more significant than the statutory law of England. This is mainly due to the existence of a whole system of constitutions: federal, existing for more than two hundred years, largely outdated but still playing a significant role, and state constitutions of different age. Despite the significant influence of European legal systems, Muslim law remains an independent legal family with a serious impact on millions of people in all parts of the world.